2011
DOI: 10.1021/nn202699t
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide: A Nonspecific Enhancer of Cellular Growth

Abstract: There have been multiple conflicting reports about the biocompatibility and antimicrobial activity of graphene oxide. To address this, we conducted a study to characterize the antimicrobial properties of graphene oxide (GO) and its biocompatibility with mammalian cells. When GO was added to a bacterial culture at 25 μg/mL, the results showed that bacteria grew faster and to a higher optical density than cultures without GO. Scanning electron microscopy indicated that bacteria formed dense biofilms in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
461
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(496 citation statements)
references
References 29 publications
(60 reference statements)
34
461
1
Order By: Relevance
“…Recently, Ruiz et al 56 showed that bacteria grew faster and to a higher optical density when GO was added to a bacterial culture at 25 µg/mL than cultures without GO, and also they explained bacterial growth on filters coated with 25 and 75 µg of GO grew two and three times better than on filters without GO. Liu et al 32 observed strong antibacterial activity of four types of graphene-based materials (Gt, GtO, GO, and rGO).…”
Section: Effect Of Gt Gto Go and Rgo On Bacterial Growthmentioning
confidence: 99%
“…Recently, Ruiz et al 56 showed that bacteria grew faster and to a higher optical density when GO was added to a bacterial culture at 25 µg/mL than cultures without GO, and also they explained bacterial growth on filters coated with 25 and 75 µg of GO grew two and three times better than on filters without GO. Liu et al 32 observed strong antibacterial activity of four types of graphene-based materials (Gt, GtO, GO, and rGO).…”
Section: Effect Of Gt Gto Go and Rgo On Bacterial Growthmentioning
confidence: 99%
“…Ruiz [116] studied the antibacterial, bacteriostatic and cytotoxic properties of GO in both bacteria and mammalian cells. The results show that bacteria in 25 μg/mL colloidal GO Luria-Bertani (LB) media grow faster than in LB media without colloidal GO, indicating that GO may be acting as a scaffold for bacterial attachment, proliferation and biofilm formation.…”
Section: Biological Property Of Go-based Materialsmentioning
confidence: 99%
“…Multiple recent studies have focused on the use of graphene and graphene composites in biomedical applications. 133,[228][229][230][231] From these studies, as well as other cytotoxicity studies on graphene and related compounds, 69,232-251 we are able to draw some conclusions regarding graphene's biological toxicity.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 91%
“…These studies have shown the use of graphene in microbial fuel cells, 249 graphene as a scaffold for bacterial growth, 228 as well as the use of bacteria as a graphene oxide reducing agent. 250,251 Various in vitro toxicity studies have been conducted to determine the toxicity of graphene towards cancer [234][235][236][237][238] and human cell lines.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 99%